Structural organization of yeast and mammalian mediator complexes - Dotson, Michaela R. (The National Academy of Sciences, 2000)
Structures of yeast Mediator complex, of a related complex from mouse cells and of thyroid hormone receptor-associated protein complex from human cells have been determined by three-dimensional reconstruction from electron micrographs of single particles. All three complexes show a division in two parts, a “head” domain and a combined “middle-tail” domain. The head domains of the three complexes appear most similar and interact most closely with RNA polymerase II. The middle-tail domains show the greatest structural divergence and, in the case of the tail domain, may not interact with polymerase at all. Consistent with this structural divergence, analysis of a yeast Mediator mutant localizes subunits that are not conserved between yeast and mammalian cells to the tail domain. Biochemically defined Rgr1 and Srb4 modules of yeast Mediator are then assigned to the middle and head domains.